A more realistic performance evaluation of solar convertors: the need for exergic spectral analysis of radiative heat transfer. (2nd September 2020) - Arya, Amir; Yaghoubi, Mahmood; Jafarpur, Khosrow
Solar energy harvesting devices have got considerable attention and significant efforts have been made to optimise their performance recently. Exergy analysis is a useful approach to evaluate the thermodynamic behaviour of the related system. However, the exergy theory of radiation is not well developed, yet. The conventional theory of Petela for radiation exergy, is not well applied for solar energy convertors which are working in a certain spectrum bandwidth such as photovoltaic (PV) panels. More specifically, the inlet exergy of PVs are generally assumed to be the full spectrum exergy, which is not the case for the available panels. In the present study, the exergy fraction functions are presented. As an application, the second law efficiency of various PV panel types are estimated based on the proposed method. It is shown that up to 55% error for exergic efficiency of PV panels might occur by using the conventional relation.